2019
DOI: 10.14744/ijmb.2019.41736
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diagnostic accuracy and optimal cut point of blood lead levels on serum proteins among Pb-exposed workers from Pb-battery plant.

Abstract: Assessment of diagnostic accuracy and optimal cut points of blood lead levels on serum proteins among workers exposed to Pb at a lead battery plant L ead (Pb)-binding proteins originate in the kidney, brain, erythrocytes, liver, and lung [1]. Proteins related to heme synthesis, calcium metabolism, and neurotransmission are associated with Pb poisoning [2]. Systemic effects of hypertension, frank anemia, cognitive deficits, infertility, immune imbalances, delayed skeletal and deciduous dental develop-Objectives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that lead-exposed subjects exhibited low total protein levels than controls. 34,35 Most proteins have prosthetic groups composed of calcium and zinc, making them susceptible to interaction with lead, thereby affecting the level of specific proteins such as enzymes, albumin, hormones, drug/metal-binding proteins, and the cellular processes involved. 36 Further, several studies have reported the influence of high BLLs on hematological impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that lead-exposed subjects exhibited low total protein levels than controls. 34,35 Most proteins have prosthetic groups composed of calcium and zinc, making them susceptible to interaction with lead, thereby affecting the level of specific proteins such as enzymes, albumin, hormones, drug/metal-binding proteins, and the cellular processes involved. 36 Further, several studies have reported the influence of high BLLs on hematological impairment.…”
Section: Discussionmentioning
confidence: 99%